PELAKSAAN MODEL HALAQAH PENDIDIKAN AGAMA ISLAM DI SURAU KELURAHAN 13 ULU PALEMBANG - Ahmad Badril Umam; Alimron Alimron; Sukirman Sukirman (PAI RAFAH, 2020)
In Kelurahan 13 Ulu Palembang there are many small mosque / langgar / surau, which are used as places of worship as well as places of religious learning for the surrounding community and the general public. As a place to study Islam they usually call it majlis halaqah, majlis ta'lim or majlis dhikr and others or in other words as non-formal education which has made a very meaningful contribution to the congregation or students to be able to master science - Islamic and practice it well and perfectly in everyday life.This study will use qualitative data types, namely the type of data in the form of description by gathering and analyzing a sentence (whether written or oral) of things done by humans. This research uses qualitative data type, namely the type of data in the form of the description as a research method social science that collects and analyzes a sentence (whether written or oral) and things are done by humansLearning activities as the most important part of education, where education actually aims to prepare people for change that requires the power of the mind, awareness, and creativity. And education is not limited to a certain age, but carried out throughout life, no exception to religious study groups or majlis ta'lim in Surau-Surau or langgar in Kelurahan 13 Ulu Palembang.